CEDAW Right of non-discrimination and State Obligations in connection to Trafficking in Women - Bistra, Netkova; Zejneli, Ismail (Advances in Social Sciences Research Journal, 2016)
Trafficking in human beings as a practice mostly involves women and is gender determined. Discrimination against women is both a push factor and a product of trafficking in women. The CEDAW (Convention for the Elimination of all forms of Discrimination of Women)is the central reference point in the context of the right to be free from discrimination regarding trafficking in women, since it is an instrument that deals exclusively with gender discrimination in an encompassing way. In 1979, the CEDAW addressed the issue of trafficking in women. This pivotal Convention for the affirmation and implementation of women’s human rightssets out to assure respect for the human rights of women through elimination of all forms of discrimination against them, and thus it recognized trafficking of women as a product of the ongoing discrimination against women. CEDAW distinguishes between negative and positive obligations of states in addressing discrimination against women. It developed a typology of state obligations: the obligation to respect, fulfil and protect with respect to trafficking of women, and women victims. On the bases of the theoretical background the scope of application and the concept of the right affected by the practice of trafficking was established and analysed. The relevant state obligations with respect to the right to be free from discrimination affected by the practice of trafficking and the breaches of obligations in the context of trafficking that amounted to the violations of the right were identified, thus connecting it to the set of positive state obligations under CEDAW and the possible prevention and protections actions that derive from those international standards.